Candidate's Statements of Qualifications for the Primary Election on June 2, 1970 (1970)
This document is a page from the June 2, 1970 Primary Election Voter's Pamphlet containing nonpartisan candidates' statements of qualifications. It includes biographical information, education, professional background, and experience for candidates running for Ventura County judicial offices (Superior Court and Municipal Court), Coroner and Public Administrator, and Sheriff. The statements were submitted and paid for by the candidates and are printed as authorized by law.